The role of ketotifen in the prevention of testicular damage in rats with experimental unilateral undescended testes - Acikgoz A; Asci R; Aydin O; Çavuş H; Donmez G; Buyukalpelli R (Dove Medical Press, 2014)
Abdullah Acikgoz,1 Ramazan Asci,2 Oguz Aydin,3 Hikmet Çavuş,4 Gamze Donmez,5 Recep Buyukalpelli2 1Department of Urology, School of Medicine, Kemerburgaz University, Istanbul, Turkey; 2Department of Urology, 3Department of Pathology, School of Medicine, Ondokuz Mayis University, Samsun, Turkey; 4Department of Urology, Medical Park Samsun Hospital, Samsun, Turkey; 5Department of Pathology, School of Medicine, Ondokuz Mayis University, Samsun, Turkey Abstract: The aims of this study conducted on rats were to determine mast cell (MC) proliferation on undescended testes (UDTs); whether there is a correlation between MC proliferation and testicular damage; and whether testicular damage can be prevented with administration of an MC blocker. Sixty-five newborn male rats were divided into three groups. During the neonatal period, unilateral UDTs were experimentally induced in Group 2 and Group 3. The rats in Group 3 were given 1 mg/kg/day ketotifen orally until the end of the study. Groups 2 (n=30) and 3 (n=15) were divided into groups of ten and five rats, respectively, each of which underwent bilateral orchiectomy in either the prepubertal, pubertal, or adult period. Group 1 (n=15) underwent a sham operation followed by bilateral orchiectomy, with five rats in each of the prepubertal, pubertal, and adult periods. Testicular MCs in the interstitial and subtubular areas, biopsy scores, interstitial connective tissue, seminiferous tubule (ST) diameters, and the basement membrane thickness of STs were evaluated. In Group 2 the ST diameters in the UDTs decreased, the number of MCs in the interstitial and subtubular areas increased, ST basement membranes thickened, and spermatogenesis decreased. The number of MCs in the interstitial and subtubular areas of the descended testes increased and spermatogenesis decreased. In Group 3, the number of MCs in the interstitial and subtubular areas decreased. In unilateral UDTs, the number of MCs in the interstitial and subtubular areas increased in both testes. Fibrosis developed in the ST basement membranes and interstitial areas, and spermatogenesis deteriorated. Testicular fibrosis may be prevented with administration of an MC blocker. Keywords: rat, unilateral undescended testis, MC, spermatogenesis, atrophic testis